Riqueza, abundancia y caracterización de la población avifaunística del área de protección del río Bermúdez como insumo para la creación de un corredor biológico interurbano, Heredia, Costa Rica. - McQueen-Blanco, Jean Karl (2019)
This study focuses on knowing the richness and abundance of the avian population associate with one urban microbasin, also characterize the species through the use of trophic guilds and their forest dependence. Four sites were selected within the urban area and 4 within the peri-urban area, in each site were placed 5 counting points with a defined radius of 50 meters. The points were placed parallel to the strip of riverside plants, separated by 150 meters each, for a total of 40 counting points within the micro-basin. A total of 171 bird species have been found and are distributed in 41 families. It is considered a high richness for the city compared with other studies; In addition, a higher proportion of omnivores are reported compared to other guilds and a majority of species with a preference for forest fragments located in the peri-urban zone than other sites.